Takhrij and Syarah Hadith of Agrotechnology Utilization of land - Alya Aghni Rahmawati; Wahyudin Darmalaksana; Yati Setiati Rachmawati; Casram Casram (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith with regard to agrotechnology. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The result and discussion of this research is that land is a gift from Allah SWT which we must take advantage of. The conclusion of this study is the takhrij and syarah hadith of the Prophet SAW regarding the use of land which is a provision for worshiping Allah SWT for those who make good use of it.